Monolithic Perovskite‐Silicon Tandem Solar Cells: From the Lab to Fab?. Issue 24 (7th April 2022) - Fu, Fan; Li, Jia; Yang, Terry Chien‐Jen; Liang, Haoming; Faes, Antonin; Jeangros, Quentin; Ballif, Christophe; Hou, Yi
Abstract: This review focuses on monolithic 2‐terminal perovskite‐silicon tandem solar cells and discusses key scientific and technological challenges to address in view of an industrial implementation of this technology. The authors start by examining the different crystalline silicon (c‐Si) technologies suitable for pairing with perovskites, followed by reviewing recent developments in the field of monolithic 2‐terminal perovskite‐silicon tandems. Factors limiting the power conversion efficiency of these tandem devices are then evaluated, before discussing pathways to achieve an efficiency of >32%, a value that small‐scale devices will likely need to achieve to make tandems competitive. Aspects related to the upscaling of these device active areas to industry‐relevant ones are reviewed, followed by a short discussion on module integration aspects. The review then focuses on stability issues, likely the most challenging task that will eventually determine the economic viability of this technology. The final part of this review discusses alternative monolithic perovskite‐silicon tandem designs. Finally, key areas of research that should be addressed to bring this technology from the lab to the fab are highlighted. Abstract : This work reviews the recent developments in the field of perovskite‐silicon tandems, explores the feasibility to elevate efficiency to >32%, analyzes the upscaling technology being compatible with the current silicon technology, and discusses the pathways to prolong its stability.